Oiled territories: theoretical category and a case study in Gobernador Ayala (La Pampa-Argentina) (Huellas, 2015)
From a theoretical and analytical perspective, the concept of oiled territories is used to define a series of conditions and determining factors that take place in certain geographical spaces as a result of the dramatic development of hydrocarbon production, part and parcel of the capitalist model of flexible accumulation. In theprovinceofLa Pampa(Argentina) oil and gas exploitation enjoy a boom which derives from legislation which allowed for the privatization or concession of exploitation and exploration areas by private companies since the 1990s but more strongly after Law 26.197 was passed and came into force, granting the provinces the administration of the oilfields. In this context, an accelerated process of transformation in the territorial components took place, which can be detected not only in the material changes but also in the cultural and everyday life changes, giving rise to new dynamics in the field of power relations and conflict, producing in turn territorial tensions made evident in the different intentionalities of intervention.Departing from the theoretical-conceptual definition, then, such an approach is applied to a case study in an operation area called Gobernador Ayala III, located on the southern-west end of theprovinceofLa Pampaon the banks of theColorado River, an area where changes produced by this development altered the everyday life conditions of the rural inhabitants.
Keywords: Oiled territories; conflict; the dispossessed; Gobernador Ayala